Factors Affecting Unemployment Rates In Indonesia - Adianita, Happy; Susilowati, Dados; Karisma, Devia Anindita Putri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This study aims to identify the influence of education quality, labor absorption, and poverty level on the unemployment rate. The method used in this study is quantitative descriptive, utilizing secondary data in the form of a cross-section from the Central Statistics Agency (CSA) website. The population in this study was 34 provinces in Indonesia. The sampling technique applied was saturated sampling, where the entire population of 34 provinces was sampled. The data analysis used multiple linear regression for data testing. The study's findings indicate that individual testing shows a more diverse picture; education quality and poverty level do not affect the unemployment rate, and labor absorption positively affects the unemployment rate. This study has implications for the complexity of the unemployment issue and the importance of a holistic approach in formulating policies to address these problems. These results can be a reference for related parties to develop more effective policies and programs in dealing with unemployment problems.